Critical Decisions in Negotiation: A New Video Resource for Teaching Negotiation. Issue 4 (10th October 2013) - Bordone, Robert C.; Carr, Chad M.
<x xml:space="preserve">Abstract</x> Negotiation teachers have many goals. Improving a student's skills of observation, analysis, and diagnosis, and building his or her capacity to translate theory to practice are often among the most important of these. The Critical Decisions in Negotiation video project seeks to advance these goals. The video features four sets of professionals negotiating a simulation, and then debriefing key parts of the negotiation afterward with Professor Robert Bordone to reveal the thought processes that motivated particular behavioral moves. Bordone provides commentary after each sequence to connect theory to practice. The video project is organized around three broad themes — openings and process, dealing with difficult tactics, and active listening and effective assertion. Key features include a detailed teaching note, unscripted professionals in action, and unvarnished reviews by the negotiators themselves after the fact. The method employed by the Critical Decisions in Negotiation video represents a valuable new pedagogical tool for negotiation instructors and students alike.